2023
DOI: 10.3389/fimmu.2023.1132045
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the impact of systemic lupus erythematosus on oocyte and embryo development as well as female fertility

Abstract: BackgroundSystemic lupus erythematosus (SLE) is often associated with adverse reproductive outcomes. But it’s currently unclear regarding the role of SLE in oocyte and embryonic development. Also, it’s controversial whether SLE has an adverse effect on fertility. There is a lack of comprehensive understanding and assessment of fertility in patients with SLE.ObjectiveThis study was aim to investigate oocyte and embryonic development as well as ovarian reserve, and clinical outcomes in SLE patients during in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Additionally, our previous work found that SLE patients also exhibit oocyte and embryonic developmental abnormalities [ 31 ], which may imply some commonalities between autoimmune diseases.Delving deeper into the potential mechanisms may enrich our understanding of their complex relationship.In relation to the clinical pregnancy, our study provides a more comprehensive assessment of clinical outcomes, and our results show that even when more embryos are transferred on average, the rates of implantation, LBR per complete cycle, and LBR per transfer are distinctly decreased in pSS patients than in comparison patients. Actually, similar to our findings, a case–control study by Priori et al reported that the average number of pregnancies in pSS patients were quite lower than normal patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our previous work found that SLE patients also exhibit oocyte and embryonic developmental abnormalities [ 31 ], which may imply some commonalities between autoimmune diseases.Delving deeper into the potential mechanisms may enrich our understanding of their complex relationship.In relation to the clinical pregnancy, our study provides a more comprehensive assessment of clinical outcomes, and our results show that even when more embryos are transferred on average, the rates of implantation, LBR per complete cycle, and LBR per transfer are distinctly decreased in pSS patients than in comparison patients. Actually, similar to our findings, a case–control study by Priori et al reported that the average number of pregnancies in pSS patients were quite lower than normal patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report here that though ARE +/- and ARE -/- female mice with mild to moderately elevated IFN-γ (respectively) ovulate, develop CL (though reduced), and whose fertilization is not impaired, there is increased CD8 + T cell infiltration in the ovary and uterus. However, unlike existing lupus mouse models, ARE -/- female mice do not get pregnant or show implantation sites, while ARE +/- female mice have reduced litter sizes, mimicking infertility phenotypes found in SLE and most autoimmune patients ( 55 , 58 , 59 ). Furthermore, we report that aberrant CD8 + T cells in the ARE +/- and ARE -/- mouse ovary and uterus acquire effector memory signatures capable of propagating self-tissue damage.…”
Section: Introductionmentioning
confidence: 86%
“…Длительное использование нестероидных противовоспалительных препаратов у больных СКВ может приводить к бесплодию, а применение высоких доз кортикостероидов провоцирует различные нарушения менструального цикла из-за воздействия на гипоталамо-гипофизарнояичниковую ось [11]. 3,3 нг/мл, р=0,001) [29]. По данным Angley M. и соавт., низкие значения АМГ у женщин с СКВ наблюдаются в 1,5-1,6 раза чаще, нежели у женщин без СКВ [30].…”
unclassified